Prioritas Perbaikan Aplikasi M-commerce dengan Importance Performance Matrix Analysis (IPMA) - Hutahaean, Hotma Antoni; Silalahi, Agustinus; Prabu Hidayat, Trifenaus; Magdalena, Maria (Prodi Teknik Industri, Fakultas Teknik - Universitas Katolik Indonesia Atma Jaya, 2025)
The utilization of mobile commerce (m-commerce) applications is closely linked to the examination of consumer loyalty. A substantial body of research underscores the significance of m-commerce services and user acceptance in enhancing customer retention. This study aims to investigate the correlation between usability and user loyalty within m-commerce platforms by applying Importance-Performance Matrix Analysis (IPMA) to identify critical areas for improvement. The research sample comprised 149 users of m-commerce applications. Findings from the IPMA indicate that the key areas for enhancement in terms of (1) loyalty include users’ ability to exercise control, the simplicity of control mechanisms, and overall ease of use; while for (2) usability, the priority aspects for improvement are error notification features, accuracy, and completeness of the application’s functionalities